Pengaruh Literasi Keuangan, Gaya Hidup dan Financial Technology Terhadap Perilaku Keuangan pada Mahasiswa Universitas Buana Perjuangan Karawang - Pebi Pebrianti; Ujang Suherman; Rengga Madya Pranata (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study was to analyze the influence of financial literacy, lifestyle, and financial technology on financial behavior in students of Universitas Buana Perjuangan Karawang. The method used is quantitative research with a descriptive verification approach, involving 100 students of Universitas Buaan Perjuangan Karawang as a sample taken through purposive sampling techniques. Data were collected through online questionnaires and multiple linear regression analysis. The results of the study indicate that financial literacy and financial technology have a positive and significant effect on financial behavior, while lifestyle has no effect on financial behavior. The results of financial literacy, lifestyle, and financial technology simultaneously have an effect on financial behavior with a determination coefficient showing 40.6% of the variation in financial behavior is influenced by the three independent variables. This study concludes that improving good financial behavior is from the level of understanding of financial literacy and the proper use of financial technology. This study implies that students can be wiser in managing finances, planning expenses, and avoiding excessive lifestyles, as well as expanding knowledge about investment to achieve higher financial literacy and good financial behavior.